Human reliability in railway engineering: Literature review and bibliometric analysis of the last two decades. (July 2022) - Ciani, Lorenzo; Guidi, Giulia; Patrizi, Gabriele
Highlights: Introduction of a systematic literature review and bibliometric analysis of human reliability in railway engineering. Analysis of the state of the art of HRA with application to railroads systems from 2000 to August 2021. Classification of the papers into five categories, and detailed discussion of each one of them. The research direction seems to be firmly established toward the analysis and review of significant accidents and the improvements of existing techniques originally developed to other fields. Abstract: Human reliability is a critical aspect during safety assessment of many complex systems. Design, installation and maintenance are some of the tasks that are still demanded to human operators, and thus they are subjected to human factor. The probability of a human error could be estimated using several Human Reliability Analysis (HRA). HRA has been firstly developed for nuclear plants, then it has widespread over many different applications. Several international standards and technical reports agree that human reliability is a central concern during safety assessment of railway-related systems. Despite many papers have already been published in HRA field, a systematic literature review and bibliometric analysis of human reliability in railway engineering is missing. This paper build upon such needs analyzing the state of the art of HRA with application to railroads systems from 2000 to August 2021. The review highlights a significant increase in the interest of HRA in railway. Recent papers do not focus on the proposal of innovative HRA methods specifically developed for railway. Instead, almost all the papers deal with the analysis of railway accidents (by a human factor and safety assessment point of view) or with the improvements of existing methods originally developed for other fields. However, the analysis of the state of the art pointed out some major gaps in the field that need to be discussed by further works.